TRANSLATION ANALYSIS ON ENGLISH COPULAR CLAUSES INTO INDONESIAN IN MARY SHELLEY’S NOVEL: “FRANKENSTEIN” - Aulia Firstiyanti (Asosiasi Dosen Muda Indonesia, 2022)
This is a research on how English copular clauses in a science fiction novel are translated into Indonesian. The first problem of this research is what kinds of English copular clauses are used, and the second is what kinds of Indonesian clauses are employed in translating them. The researcher chooses the topic since there is no formal correspondence of English copular clauses in Indonesian. The purposes of this research are to classify the English copular clauses in composing this novel and to identify the kinds of Indonesian clauses employed by the translator. The data are taken from a science fiction novel entitled Frankenstein and its translation in Indonesian entitled Frankenstein as well. The findings of this research are that dominantly the predicational clause is used by the author to write this novel; the percentage of predicational clauses is 66%. The next finding is that the translator used two categories of Indonesian clauses. They are verb clauses and noun clauses; the percentage of verb clauses is 90%; on the other hand, and the percentage of noun clauses is 10%. Keywords: translation, clauses, English copular clauses